Hubungan Manajemen Pos Pembinaan Terpadu Penyakit Tidak Menular (Posbindu PTM) dengan Kepuasan Pelayanan Lansia Kelurahan Sumbersari, Kecamatan Lowokwaru, Kota Malang - Permatasari, Cut Ananda Nur; Purwito, Lasi; Widianto, Edi (Learning Community : Jurnal Pendidikan Luar Sekolah, 2023)
The Development of Post of Non Transmitted Disease now is certainly inseparable from service provided to the elderly. This form of service affects the satisfaction of the elderly. The Purpose of this observe changed into relationship management of development post of non transmitted disease with elderly satisfaction in Sumbersari, Malang city. This research method uses correlational research with a quantitative approach. The study population was all active elderly members spread over four Post of Non Transmitted Disease with a study sample of 83 elderly using proportional random sampling technique. The result of this research from the feasibility test have a value 87.2% for management of Development Post of Non Transmitted Disease is included in the very good category, then the elderly service satisfaction have a value of 87.5% is included in the very good category. It showed that relationship between management of development post of non transmitted disease with elderly satisfaction on a correlation coefficient of 0.710 wich means is relationship between two variables is a strong relationship